PLAN DE MARKETING PARA LA EMPRESA DISTRIBUIDORA GRANDA UBICADA EN LA CIUDAD DE LOJA - Camisán, María de los Ángeles (2015)
Ecuador Current conditions have changed, customers are increasingly demanding which is why all must support the Marketing Managers for this great task of identifying market needs. Distribuidora Granda under investigation is located in the city of Loja, and is still part of the economic engine of the province of Loja 25 years, serving the market for the province of Loja, and has also dabbled in the markets of the province Zamora Chinchipe in the cantons of Zamora, Zumba, Gualaquiza and Yantzaza; in the province of El Oro in the cantons of Zaruma and Portovelo, currently it has 7,000 customers, has generated 25 job openings and distributes about 520 products, grouped in different lines of national and international origin. Inductive, deductive, analytical, and technical methods such as signing, the survey interview, observation was used to achieve them, taking a sample of 254 customers in Loja, 73 customer surveys in the province of Zamora Chinchipe and 37 customers of El Oro. At the conclusion one can say that the situation analysis first objective of this study found the following: the strengths that the Distributor are: solvency, quality of products, customer base and established sales force with experience, good market share. The weaknesses are: poor corporate advertising, lack of sales promotion, lack of training for employees, outdated description of charges, delay in dispatching and vehicle fleet UNIVERSIDAD NACIONAL DE LOJA ÁREA JURÍDICA, SOCIALY ADMINISTRATIVA CARRERA DE ADMINISTRACION DE EMPRESAS Ma. De Los Ángeles Camisán 5 In the analysis of external factors could be seen as opportunities to growing market, the large number of suppliers, the variety of businesses dedicated to training, the development of technology, skilled labor and the development of communications. Instead threats are: tariff policy, growing competition, labor law, increased unemployment, smuggling and inflation. The second objective is the development of the proposal, the Managing Director to execute the marketing plan proposed the same which has six goals and the cost is $ 228,033.14 recommended